HUBUNGAN KUALITAS SUSU DENGAN MASTITIS SUBKLINIS BERDASARKAN CALIFORNIA MASTITIS TEST DAN UJI IPB-1 PADA KOPERASI SUSU WARGA MULYA - , RICO RIZKI AJI; , drh. Heru Susetya M.P., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mastitis is a common disease in dairy cows and caused huge economic losses to the dairy farm across the globe. Some data regarding the prevalence of mastitis in Indonesia in Sukabumi, Bandung by 63%, Sukabumi, Bandung, Bogor 75.2%, Pasuruan, East Java 67%, Pasuruan, East Java 38.30, Baturaden, Central Java 55.8%, Boyolali, Central Java, 62.5% and Yogyakarta Special Region 36.90%. A total of 80 samples from 30 farmers were taken as the study sample. Samples were taken from the farm in Warga Mulya Dairy Cooperative which divided in 4 districts. District of Pakem, Turi, Ngemplak, and Tempel. Samples were examined directly on the paddle using California Mastitis Test (CMT) and IPB-1 test then results compared with the results of the examination of milk quality. The data obtained was analyzed using chi-square to measure the suitability of a decrease in the incidence of mastitis milk quality. The results showed 43 milk samples reacted positively with CMT and IPB-1 tes (prevalence 53.75%). Based on the study, positive result showed by IPB-1 test is more than CMT, it means that IPB-1 test has higher sensitivity than CMT. Milk quality test results showed 15% good results, 43.75% more than enough, enough 41.25%. After calculation of chi-square showed association between mastitis test and reduced in milk quality.